A calculation of surface roughness depending on the axial feed rate and tool nose radius when turning the 40x steel - Hong Son, Nguyen; Xuan Thinh, Hoang; Duc Trung, Do; Nguyen, Nhu-Tung (International Journal of Engineering and Technology, 2019)
This paper presents the experimental investigation of the surface roughness in turning process of 40X steel with the different insert nose radius and different axial feed rate. By analyzing the experimental results, the appropriate formula was proposed to calculate surface roughness when turning 40X steel with different value of the insert nose radius and different axial feed rate. The most suitable regression of surface roughness was an exponential regression with the confidence level is more than 97.3 %. These formulas were successfully verified by experimental results with very promising results. In comparison of predicted results, the results from previous research, and the measured results, the results of proposed formulas gave the smallest errors (9.73 % in case insert nose radius is 0.2 mm and 1.46 % in case insert nose radius is 0.4 mm). The approach method of the present study can be applied in industrial machining to improve the surface quality in turning processes of the X40 Steel.Â Â Â